Is there a divergence between the OECD Transfer Pricing Guidelines and post-BEPS interpretation of the Arm?s Length Principle in OECD materials, with emphasis on the control of risk and value creation? - Ball, Gavin (Department of Commercial Law, 2024)
This minor-dissertation contends that the arm's length principle is not being interpreted and applied in transfer pricing practice as intended by the OECD in its 2022 Transfer Pricing Guidelines (the TPG).1 Whether deliberate or unintentional, such a divergence has the potential to become permanent and has been exacerbated, accelerated, and entrenched by the OECD's work on digitalisation as part of the BEPS Project, with concomitant emphasis on the concept of value creation. Increased complexity in the OECD's guidance on the control of risk has also contributed to such divergence. Ultimately, there may be tacit recognition by the OECD itself of the economic reality of how MNE's operate and the challenges associated with applying the separate entity principle in group context. This has contributed, it is suggested, to increasing tolerance of and even promotion of profit-split approaches, both conceptually and in practice.